Charge correlations and their photoinduced dynamics in charge-ordered organic ferroelectrics - Hirotake Itoh; Hirokazu Obatake; Rina Fujiwara; Yohei Kawakami; Kaoru Yamamoto; Martin Dressel; Shinichiro Iwai (Physical Review Research, 2021)
By employing THz absorption and emission spectroscopy we were able to disentangle long-range charge order with a hundreds micrometer scale and short-range charge fluctuations that occur well above the charge-order phase transition in quasi-one-dimensional organic ferroelectrics, (TMTTF)_{2}X (X=AsF_{6}, PF_{6}, and SbF_{6}). While long-range charge order melts by photoexcitation irrespective of temperature or chemical pressure, short-range fluctuations are actually enhanced close to the charge-order phase boundary for X=AsF_{6} and PF_{6}. Our findings reveal that short-range fluctuations show various photoresponses depending on both temperature and electronic parameters, providing a design strategy for nonequilibrium states.